Dzhegonas mountain jews history and culture in the modern digital archives / datebases (source study aspect) - Vladimir Igorevich Kolesov (Кавказология, 2023)
During two decades, the Databases of digitized historical documents had come into sight, specifically WWI and WWII periods (www.gwar.mil.ru; www.obd-memorial.ru; www.podvignaroda.ru; www.pamyat-naroda.ru). It’s bringing a new momentum in the historical and ethnological studies by updating the focus on individual biographies, family stories and their network, genealogies and onomastics. The author is showcasing the potential of Databases for heuristic search on the local Mountain Jews group in Dzhegonas village, Kuban region. It is noted that there is an interaction process between the researcher and the platform, in which the platform, after providing options for the required data, can change the vector and focus of scientific search, thereby changing the object and subject of research, among other things. It is concluded that the advent of such Internet platforms of digitized documents and Databases affects the complex of sources in history and ethnology on the one hand, and influences research processes on the other.